Risk profile of cadmium in milkfish (Chanos chanos, Forskal) in the Philippines - Juan, Margret C.
Cadmium (Cd) is a naturally occurring heavy metal present in the environment at low concentrations but may increase due to anthropogenic activities. In particular, milkfish (Chanos chanos, Forskal), a widely consumed fish in the Philippines, has been reported in several studies to bioaccumulate Cd. Ingesting Cd-contaminated milkfish may pose health risks, as Cd exposure has been linked to cancer, chronic diseases, and even mortality. This study conducted a formal food safety risk profiling of Cd in milkfish (Chanos chanos, Forskal) through [1] determination of the data gaps in the risk profiling of Cd in milkfish by the Filipino consuming population; [2] identification and characterization of Cd as a food hazard; [3] estimation of dietary exposure (DE) and risks based on uncertainties, variabilities, and assumptions; and [4] determination of available risk management options for Cd in milkfish. The identified gaps were the lack of dose-response models, localized data on Cd distribution, pharmacokinetics, and health effects. Dietary exposures were estimated using consumption data from DOST-FNRI (2022) and Cd concentration data in Luzon (NCR, Regions 1, 2, 4B, and 5), Visayas (Regions 6 and 8), and Mindanao (Regions 12 and 13) from Rustia & Sales (2015). DE estimates based on average Cd concentrations in all regions were below the Provisional Tolerable Monthly Intake (PTMI) of 25 µg/kg bw/month set by JECFA (2010). However, at maximum concentrations, estimated DEs exceeded the PTMI in Region 6 for all age groups (73.3238-125.9368 µg/kg bw/month), while remaining regions remained below the threshold. Considering the computed DEs, Cd in milkfish presents appreciable risk to the Filipino consuming population, especially to infants and pre-school children. Currently, the available control measures for Cd in milkfish in the Philippines are Frozen Milkfish PNS/BAFS (66:2020) and ‘Code of Good Aquaculture Practices (GAqP) for Milkfish and Tilapia’ (PNS/BAFS 196:2017).